MMR vaccination status of children exempted from school-entry immunization mandates. Issue 46 (17th November 2015) - Buttenheim, Alison M.; Sethuraman, Karthik; Omer, Saad B.; Hanlon, Alexandra L.; Levy, Michael Z.; Salmon, Daniel
Abstract: Background: Child immunizations are one of the most successful public health interventions of the past century. Still, parental vaccine hesitancy is widespread and increasing. One manifestation of this are rising rates of nonmedical or "personal beliefs" exemptions (PBEs) from school-entry immunization mandates. Exemptions have been shown to be associated with increased risk of disease outbreak, but the strength of this association depends critically on the true vaccination status of exempted children, which has not been assessed. Objective: To estimate the true measles-mumps-rubella (MMR) vaccination status of children with PBEs. Methods: We use administrative data collected by the California Department of Public Health in 2009 and imputation to estimate the MMR vaccination status of children with PBEs under varying scenarios. Results: Results from 2009 surveillance data indicate MMR1/MMR2 coverage of 18–47% among children with PBEs at typical schools and 11–34% among children with PBEs at schools with high PBE rates. Imputation scenarios point to much higher coverage (64–92% for MMR1 and 25–58% for MMR2 at typical schools; 49–90% for MMR1 and 16–63% for MMR2 at high PBE schools) but still below levels needed to maintain herd immunity against measles. Conclusions: These coverage estimates suggest that prior analyses of the relative risk of measles associated with vaccine refusal underestimate that risk by an order of magnitude of 2–10 times.